Experimental study on consumer-technology supported authentic immersion in virtual worlds for education and vocational training - Reiners, Torsten; Wood, Lincoln; Gregory, S.; Baestians, T. (2014)
Despite significant and rapid technology improvements, educators have frequently failed to make use of the new opportunities to create more authentic learning scenarios. Virtual worlds offer an attractive proposition to create 3D representations of real business environments to provide an authentic learning activity for higher education students to take part in. However, the controls and displays are still clunky and unnatural, reducing the opportunity for students to immerse themselves in the event and focus on experiential learning. To overcome this challenge we examine the role of using a headset display that allows the user to change perspective with a flick of the head, improving their ability to ‘feel’ part of the environment, and thus increase their immersion in the activities that they are engaged in through more realistic control and improved perspective in the virtual environment. A series of experiments are conducted comparing the technology to established technologies and the level of control exerted by the learner (e.g., they either ‘control’ or they ‘passively observe’ as someone else controls). These experiments provide evidence that consumer-technology can improve immersion and equip educators with an affordable instrument to present classes that learners ‘take more seriously’.